2017
DOI: 10.1097/mpa.0000000000000845
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Predicts Severity of Acute Pancreatitis

Abstract: Increased VAT area is a strong predictor of severe pancreatitis, necrosis, and multisystem organ failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
3
32
1
2
Order By: Relevance
“…In addition, the scoring tools do not distinguish between truncal obesity and visceral obesity. Some studies showed that VAT significantly correlates with poor outcomes in AP patients [10, 1416]. Therefore, we investigated the relationship between body parameters, prognosis, and mortality in AP patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the scoring tools do not distinguish between truncal obesity and visceral obesity. Some studies showed that VAT significantly correlates with poor outcomes in AP patients [10, 1416]. Therefore, we investigated the relationship between body parameters, prognosis, and mortality in AP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yoon et al [10] found that high visceral fat with low skeletal muscle volume plays an important role in AP severity. Natu et al [16] found that VAT is closely associated with organ failure and necrosis in AP. However, there are some limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be caused by saturation of cholesterol in bile, which could consequently induce gallstone formation [42]. Moreover, visceral fat was also associated with severity of AP [43]. The level of adiponectin would paradoxically decrease due to excess viscera fat, which would subsequently increase the secretion of proin ammatory cytokines such as TNF-α and interleukin-6, and thus amplify the in ammatory response [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that visceral fat, not peripheral fat, is closely related to the formation of pseudocysts in patients with AP and SIRS. In contrast, patients with excessive visceral fat are more likely to have SAP [9]. Apart from obesity; hypertriglyceridemia is another key lipid metabolism disease that affects AP [10, 11].…”
Section: Introductionmentioning
confidence: 99%